Pedagogical Heritage of A.S. Makarenko in Modern Educational Space - BAZALEY, Elena (Journal of Education, Technology and Computer Science, 2013)
This article deals with the research of pedagogical heritage of A.S. Makarenko.He took great care of mora1 and labor upbringing of pupils. Teachingsenior pupils we think it is necessary to ensure knowledge of last epochs teacherswhose ideas are actual today. As our research is based on Makarenko’s creativeheritage we shall follow the process of pedagogical formation of a futureteacher today.